PERMASALAHAN DAN SOLUSI YANG DILAKUKAN MAHASISWA PESERTA PROGRAM KAMPUS MENGAJAR - Gunawan Tambunsaribu (Jurnal Abdi Insani, 2023)
An Indonesian government program called â€œKampus Mengajarâ€ aims to assist primary and secondary schools in overcoming many problems in the teaching system, administration, and technology adaptation experienced by students and teachers. The purposes of this study are to find out the types of problems students face when implementing the program â€œKampus Mengajarâ€ in the target schools and to find out the steps taken by students as a solution to solve the problems. The scope of this research is limited to one of the â€œKampus Mengajarâ€ target schools. This research uses a descriptive qualitative method. The research data were obtained using interviews and field notes. The respondents are six college students from different majors from different campuses in Jakarta. This study found three categories of problems faced by students in the target schools, namely: 1) problems in the field of teaching, 2) problems in the field of completeness of school administration, and 3) problems in the field of technology. This research found that the â€œKampus Mengajarâ€ program carried out by students helped students improve their learning abilities and helped teachers improve their teaching performance. The implementation of the Teaching Campus program by students is very beneficial to the target schools. Key Words: Kampus Mengajar, studentâ€™s problems, solution